Outcome in dogs with presumptive idiopathic pericardial effusion after thoracoscopic pericardectomy and pericardioscopy. (5th December 2018) - Carvajal, Jose L.; Case, J. Brad; Mayhew, Philipp D.; Runge, Jeffrey; Singh, Ameet; Townsend, Sarah; Monnet, Eric
Abstract: Objective: To report the outcome of dogs with presumptive echocardiographic idiopathic pericardial effusion treated with thoracoscopic pericardectomy and pericardioscopy. Study design: Multi‐institutional retrospective study (2011‐2017). Animals: Eighteen dogs. Methods: Records were searched for dogs with pericardial effusion and no identified cause by preoperative echocardiography and subsequent thoracoscopic pericardectomy and pericardioscopy. Collected data included presenting complaint, physical examination, laboratory results, imaging, and operative findings. Follow‐up was obtained via telephone interview and/or recheck examination. Results: No evidence of mass lesions or cause for the effusion was identified in any of the dogs by preoperative echocardiography. Nine dogs had unremarkable pericardioscopic examination results. Nine dogs had pericardioscopic abnormalities consistent with masses, nodules, or adhesions. Median survival time (MST) for the 9 dogs with abnormalities identified by pericardioscopy was 66 days, whereas MST for the 9 dogs with unremarkable pericardioscopic examination results was not reached ( P  = .0067). Median survival time for dogs based on histopathologic diagnosis alone was not different between dogs with a diagnosis of neoplasia and dogs with a diagnosis of pericarditis ( P  = .1056). Among dogs with lesions identified during pericardioscopy, MST did not differ between those with a diagnosis of malignancy and those with a diagnosis of pericarditis ( P  = .78). Conclusion: Dogs with presumptive idiopathic pericardial effusion without evidence of masses, nodules, and/or adhesions during thoracoscopic pericardectomy and pericardioscopy lived longer than dogs in which abnormalities were identified during pericardioscopy. Clinical significance: Thoracoscopic pericardectomy/pericardioscopy and targeted biopsy of the pericardium and pleura are recommended in dogs with echocardiographic idiopathic pericardial effusion.